Operation characteristics of a bubbling fluidized bed heat exchanger with internal solid circulation for a 550-MWe ultra-supercritical CFB boiler. (1st February 2020) - Li, Dongfang; Cai, Runxia; Zhang, Man; Yang, Hairui; Choi, Kyeong; Ahn, Seokgi; Jeon, Chung-Hwan
Abstract: The world first 550-MWe ultra-supercritical circulating fluidized bed (CFB) boiler is designed with integrated recycle heat exchangers (INTREX) and internal solid circulation. In this research, in order to investigate the heat transfer behavior and the significance of the internal circulation, the operation characteristics of the four INTREXes as final superheaters including heat transfer coefficients and ash flow rates under different load conditions are experimentally studied. The calculation of ash circulating rate shows that as the boiler load decreases, the furnace bed temperature and the circulating ash temperature in the loop seal decrease, while the flow rate of the internal circulation and its proportion to the total solid flux increase as the boiler load decreases. In particular, under 60% load condition, the internal flow rate is found to be higher than that of external flow rate for the two INTREXes located in front of the middle sections of the furnace. This indicates that the internal circulation is of more significance in the low-load condition than in the high-load condition. The key factor determining the internal-circulation flow rate is found to be the bed pressure drop in the furnace. The phenomenon of non-uniform distribution of solid flux among INTREXes is also discussed. Highlights: Experimental tests were performed on a 550-MWe USC CFB boiler designed with INTREX. Internal circulation is found to be significant under a low-load condition. Heat transfer in the INTREX is found to be enhanced by the internal circulation. The flow rate of internal circulation is found to be increased as load decreases.